Long-term quality of life among breast cancer survivors eligible for screening at diagnosis: a systematic review and meta-analysis. (October 2021) - Moshina, N.; Falk, R.S.; Hofvind, S.
Abstract: Objectives: This study aimed to explore the long-term quality of life (QoL) among breast cancer survivors eligible for mammographic screening at diagnosis and compare that to QoL among women with no history of breast cancer. Study design: Systematic review and meta-analysis. Methods: A systematic review of randomised controlled trials and observational studies published between January 2000 and July 2019 was performed. Eight studies were included in the review. Six studies with QoL measurement scales (0–100) were included in the meta-analysis. We used fixed and random effects models to obtain Cohen's d with 95% confidence interval (CI). Heterogeneity among studies was evaluated by the I 2 statistics. Results: Information about 6145 breast cancer survivors diagnosed between 1995 and 2012 and followed for >1–10 years was analysed. Four studies used SF-36/RAND-36, three studies used EORTC QLQ-C30, one study used FACT-G and one study used FACT-B. The mean score of QoL for breast cancer survivors varied from 63.0 (RAND SF-36, 0–100) to 110.5 (FACT-B, 0–123). Two studies showed better, three studies showed similar and two studies showed poorer mean scores for breast cancer survivors compared with women with no history of breast cancer. The meta-analysis showed no significant differences in QoL for breast cancer survivors compared with women with no history of breast cancer (Cohen's d = −0.07, 95% confidence interval [CI] −0.14 to 0.00 and I 2 = 83.7% for the fixed effect model; Cohen's d = −0.00, 95% CI −0.18 to 0.17 and I 2 = 82.4% for the random effects model). Conclusion: QoL did not differ between breast cancer survivors eligible for mammographic screening at diagnosis and followed for >1–10 years and women with no history of breast cancer.